El IMB como modelo de información, motivación y habilidades conductuales, para identificar prácticas sexuales en estudiantes de grado 11, matriculados en una institución educativa de carácter público ubicada en Cali. (2023)
The present investigative work is oriented from the IMB model, it consists of describing three variables that are information, motivation, and behavioral skills in relation to the sexuality of students in grades 11, between the ages of 16 and 18 belonging to an educational institution of public character located in the city of Cali. The research aims to know what information 11th grade students have, and to know their most recurring sources 12 when they want to talk about sexuality, to know motivational aspects in relation to sexuality and to describe behavioral skills. This work makes a quantitative description in which to try to identify those risk factors that exist regarding sexuality in which many of these generate misinformation in many aspects, for them emphasis is placed on the importance of education in children and adolescents, considering that both the family environment and the education environment are shapers of the education of children and adolescents.